Direitos políticos do imigrante: análise político-jurídica sob a perspectiva brasileira - Cristino, Fernanda da Rosa (2016)
In the face of the importance of the immigrant for the development of a sustainable society, considering the diversity of its dimensions and the Brazilian s commitment in supply its people need; it is justified the necessity to analyze politically and juridically the immigrant political rights in the country. Considering its multicultural formation and the democratic nature defended, the development of a politic guided by the intercultural relations, aiming to the development of a plural society is crucial. The plurality requires all the citizens participation in the decision processes. That is why this study has searched to analyze the state of art of the immigrant political rights in the country, specifically in relation to the suffrage, exercise that concretize the citizenship, the popular sovereignty. The Brazilian positioning about the immigrant vote prerogative was questioned, as well as the contribution of the legislation of the other countries from Latin America for the development of an adequate legislation. A dialectical approach was chosen, due to the study from the contradictions and the antagonism of the system for the formal recognition of the right to vote. The analysis and the documents interpretation and data follows the qualitative model, on account of the psychosocial explanatory focus, for the context comprehension. The data were obtained through bibliographic research of the migration profiles, Federal Constitutions and migratory legislation of the countries involved; but, for this purpose, with the technical supply of summaries, reviews, annotations. The analysis was presented in two chapters: the construction of the political participation of the immigrant in Brazil and about the recognition of the political rights of the immigrant in Latin America . In the first chapter there was the scope to expose the theoretical substantiation that allows to recognize and comprehend the complexity that settles the immigrant in the field of the sociobiodiversidade rights, as well as the rights deprivation which the country is exposed. In the second, it was presented models developed in the other Latin America countries. It was noticed that Brazil is about to institute a new political mark in immigration represented by PL288/2013, sent to Cãmara de Deputados (PL 2516/2015). However, this still copy the state power concentration, being omissive about the immigrant vote, about the Human Right to Immigrate. Not many countries in Latin America have developed their perception about the human rights comprehension beyond the homogeneity and the democracy as plurality. Between the analysed countries, the Argentinian and Bolivian model are closer to the ideal project. It is expected that the exposure may contribute for a new political migratory mark indeed effective.